2018
DOI: 10.1080/19390211.2018.1451940
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Tocopherol Supplementation Restricts Aluminium- and Ethanol-Induced Oxidative Damage in Rat Brain but Fails to Protect Against Neurobehavioral Damage

Abstract: The concurrent presence of oxidative stress (OS) and aluminium exposure is an inducer of neurodegenerative changes. Aluminium can augment OS in a pro-oxidant dominant condition. Antioxidative property of α-tocopherol may be useful in restricting these degenerative changes in the brain. OS parameters are tested in frontal cortex (FC), hippocampus (HC), and cerebellum (CL) of α-tocopherol-supplemented (5 IU/day) male Wistar rats exposed to aluminium (10 mg Al/Kg/day; "Al"), ethanol (0.6 g ethanol/Kg/day; "Et"), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Maintenance of systemic, organ or regional GSH level by vitamin E, TRF or T3 in presence of oxidative stressor had been reported times and again. [23,32,[37][38][39][40][41][42] Increases in cerebellar GSH level were noticed in the ST3 group (statistically significant) and TT3 group (statistically significant) in comparison to NT3 and PT3 groups of Et-0 phase of current study. However, in presence of Et exposures, TT3 group abled to maintain the level of cerebellar GSH while ST3 group failed to do so.…”
Section: Biochemical Parametermentioning
confidence: 53%
“…Maintenance of systemic, organ or regional GSH level by vitamin E, TRF or T3 in presence of oxidative stressor had been reported times and again. [23,32,[37][38][39][40][41][42] Increases in cerebellar GSH level were noticed in the ST3 group (statistically significant) and TT3 group (statistically significant) in comparison to NT3 and PT3 groups of Et-0 phase of current study. However, in presence of Et exposures, TT3 group abled to maintain the level of cerebellar GSH while ST3 group failed to do so.…”
Section: Biochemical Parametermentioning
confidence: 53%
“…This finding agrees with the work of Dwivedi and Tomar (42), which also showed significantly severe hypokinesia both in terms of latency to leave the starting square of the OFT and the number of lines crossed. However, Nayak et al (43) demonstrated the failure of vitamin E to protect against neurodegeneration in rat brains at a given dose, making the rats perform poorly in some motor coordination tasks. There was also a significant increase in the number of lines crossed following the co-administration of both vitamins compared to the reserpine group, and this effect was more profound than that observed following single administrations.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure sources for Al include geochemical, industrial, anthropological and uses in daily life. [1,2] Enhancement of Al exposure is caused from various eatables, medications, avoidable deliberate / intentional uses of topically applied cosmetics and hygiene products like deodorants and toothpaste. [3] In addition, some occupational groups are specifically subjected to high level of Al exposures.…”
Section: Introductionmentioning
confidence: 99%